Concomitant Medication Effects on Immune Checkpoint Inhibitor Efficacy and Toxicity - Sieber, Brendan; Strauss, Julius; Li, Zihai; Gatti-Mays, Margaret E. (Frontiers in Oncology, 2022)
There are multiple approved indications for immune checkpoint inhibitors (ICI) in patients with advanced solid tumors. Polypharmacy, defined as the use of ≥ 5 medications, is common among cancer patients. The impact of these non-oncologic medications on ICI efficacy or the development of side effects, specifically immune related adverse events (irAEs), is unclear. Recent clinical studies investigating the connection between concomitant medications and ICI efficacy have produced conflicting results. A systematic literature search was performed on PubMed to identify published clinical studies evaluating the impact of metformin, angiotensin-converting-enzyme inhibitor (ACEi), angiotensin receptor blockers (ARBs) and aspirin on ICI outcomes and toxicity in patients with advanced solid tumors. Clinical outcomes assessed included overall response rate, progression free survival, overall patient survival and the development of adverse events, specifically irAEs. A total of 10 retrospective studies were identified. Most studies reported a small percentage (range 8% to 42%) of their study population taking the concomitant medications of interest. Collectively, the studies did not identify a significant impact on ICI efficacy with concomitant medication use. In addition, the impact on irAEs was rarely reported in these studies but no significant group effect on reported toxicities or irAEs was found. This review provides a comprehensive analysis of current clinical studies and illustrates potential alterations in the tumor microenvironment induced by the medications. Given the high occurrence of polypharmacy among patients with advanced cancer, gaining a better understanding of the impact of non-oncologic medications on immunotherapy is necessary to improve ICI efficacy and reduce toxicity.